Primary ciliary dyskinesia as a rare cause of male infertility: case report and literature overview - Novák, Jan; Horáková, Lenka; Puchmajerová, Alena; Vik, Viktor; Krátká, Zuzana; Thon, Vojtěch (Basic and clinical andrology, 2024)
BACKGROUND: Primary ciliary dyskinesia (PCD) is a heterogenous disease caused by mutations of miscellaneous genes which physiologically play an important role in proper structure and/or function of various cellular cilia including sperm flagella. Besides male infertility, the typical phenotypes, based on decreased mucociliary clearance, are lifelong respiratory issues, i.e., chronic bronchitis leading to bronchiectasis, chronic rhinosinusitis, and chronic otitis media. Moreover, since motile cilia are important during embryological development in the sense of direction of gut rotation, 50% of affected individuals develop situs inversus - so-called Kartagener's syndrome. CASE PRESENTATION: We present two cases of PCD as a rare cause of male infertility. CONCLUSIONS: Primary ciliary dyskinesia should be suspected in infertile males having (sub)normal sperm concentration values with persistent zero motility together with patient's and/or family history of respiratory symptoms like bronchiectasis, chronic cough, rhinitis, recurrent sinusitis, and otitis media. Due to more than 50 identified mutations until now, the causal mechanism of male infertility is miscellaneous and not in all cases known in detail. Besides impaired sperm motility, other mechanisms significantly decreasing efficacy of assisted reproduction techniques play a pivotal role. Thus, proper diagnostic work-up including, among others, sperm DNA fragmentation, is mandatory to avoid ineffective treatment burden.
Keywords: Primary ciliary dyskinesia; Immotile sperm; Infertility; Kartagener’s syndrome